Does size matter in the hedge fund industry? - TEO, Song Wee Melvyn (Institutional Knowledge at Singapore Management University, 2009)
We document a negative and convex relationship between hedge fund size and future risk-adjusted returns. Small hedge funds outperform large hedge funds by 3.65 percent per year after adjusting for risk. This over performance is not driven by fund age, leverage, serial correlation, or self-selection biases. The capacity constraints manifest across various investment styles and regions. In particular, they are strongest for funds managed by multiple principals who trade small, illiquid securities, suggesting that the observed diseconomies can be traced to price impact and hierarchy costs (Stein, 2002). While investors direct disproportionately more capital to smaller funds, they do not do so quickly enough to eliminate this size effect. Interestingly, the capacity constraints facing individual hedge funds do not extend to funds of hedge funds.